Gemlik Körfezi Çökellerinde Ağır Metal Ve Organik Kirliliğin Zaman İçindeki Evrimi - Albut, Gülüm (Fen Bilimleri Enstitüsü, 2015)
Marmara Denizi’nin doğusunda yer alan Gemlik Körfezi en derin yeri -113 m olan yarı kapalı bir havza olup, drenaj alanında pek çok endüstriyel ve evsel atık alması sebebiyle antropojenik kirlilik riski altındadır. Bu çalışmada Gemlik Körfezi’nin  -71 ile -105 m aralığındaki su derinliğinden alınmış üç karotta yapılan jeokimyasal analizlerle ağır metal kirliliğinin ve organik kirliliğin boyutları ve zamansal gelişimi araştırılmıştır.  Karotlarda µ-XRF karot tarayıcısı ile çoklu element, çok sensörlü karot log alıcısı (MSCL) fiziksel özellikler ve ICP-MS yöntemi ile ağır metaller analiz edilmiştir. Çökellerin toplam organik karbon (TOK) ve toplam inorganik karbon (TİK) analizleri ile organik maddenin δ13C ve δ15N, C ve N element analizleri yapılmıştır. Karotların tarihlendirilmesi radyonüklid (210Pb ve 137Cs) ve hızlandırılmış kütle spektrometresi (AMS) radyokarbon yöntemiyle gerçekleştirilmiştir.  İnce taneli homojen koyu gri-kahverengi çamurdan oluşan M-17, MNTKI-13 ve M-18 karotları, sırasıyla son 250, 260 ve 200 yılı kapsamakta ve üst kısımlarında 1985 – 1995 yılları arasında çökelmiş kokolit laminalı bir birim içermektedir. Ayrıca MNTKI-13 karotunda 1930 ve M-18 karotunda 1985 yıllarında olasılıkla Kocadere deltasından taşınmış iki kütle akması birimi tespit edilmiştir. Kütle akması birimlerinde Ti ve Zr zenginleşmesine karşın; Th, La, Nb ve Rb’deki fakirleşme, kaba silt tane boyundaki bu birimlerin rutil, titanit ve zirkon gibi ağır mineral içeriğinin zengin olmasından ileri gelmektedir. Karotların kokolit laminalı biriminde % 4’e varan TOK içeriğindeki artış, burada yaklaşık olarak 1965’te oluşan oksijensiz dip suyu koşullarından hemen sonra başlamıştır. Yaklaşık 1995 sonrası çökellerdeki organik maddenin kökeninin karasal olmasına karşın; 1985-1995 yılları arasındaki organik maddenin kökeni denizeldir. Kokolitli birimin çökelmesine de neden olan bu dönemdeki alg patlamaları, endüstriyel ve evsel atık kaynaklı besin elementi (P ve N) girdisine ve ötrifikasyona işaret etmektedir. δ15N değerleri 1930’dan günümüze olan zaman aralığında göreceli olarak daha yüksektir. Özellikle son 40 yılda körfezde bol besin elementi olduğunun bilinmesine karşın; nitrojen izotop oranının yüksek olması denitrifikasyon sürecinin baskın olduğunu göstermektedir. K, Rb ve Li’un 1840-1980 yılları arasında göreceli olarak zenginleşmesi, bu yıllar  arasında yüksek erozyona ve kurak bir iklime; son 40 yıl içerisinde fakirleşmesi ise  azalan erozyona ve yağışlı bir iklime işaret etmektedir. As, Sb, Bi, Cu, Pb, Zn ve Cd  ve Th konsantrasyonları yaklaşık 1975 yılından itibaren antropojenik olarak hızla  artmaktadır. Cd önemli derecede zenginleşme gösterirken (zenginleşme faktörü, EFmax=6), Zn ve Sb orta derecede zenginleşme göstermektedir (EF= 2.2 – 2.3). Metal değerleri 1980’den itibaren eşik değerlerini aşmaya başlamıştır. Mo, 1965’ten itibaren, kısmen anoksik dip suyu koşullarının gelişmesi ve antropojenik girdilerle birlikte artmaya başlamış ve çok yüksek miktarda zenginleşme göstermiştir (EFmax= 50). Sb, S (EFmax = 3.6) ve U (EFmax= 3) da kısmen diyajenetik, kısmen antropojenik kirlilik nedeniyle Mo’e göre daha az zenginleşmiştir.

Gemlik Gulf, which is a semi- enclosed inlet with maximum depth of 113 m in the eastern part of the Sea of Marmara, is under the risk of anthropogenic pollution from different industrial and municipial pollution sources in its drainage basin.  In this study, the extent and temporal evolution of the heavy metal and organic pollution were investigated using a wide range of analyses of three cores located in different water depths ranging from -71 m to -105 m. The cores were analyzed using µ-XRF core Scanner, Multi Sensor Core Logger (MSCL)  and Inductively Coupled Plasma - Mass Spectrometry (ICP – MS) for sediment metal concentrations. analysis of δ13C and δ15N mass spectrometric and elemental C and N analyses of bulk oganic matter and total organic carbon (TOC) and inorganic carbon (TIC) analyses of sediments were also carried out. The chronology of the cores were determined using radionuclide (210Pb and 137Cs) and Accelarated Mass Spectrometry (AMS) radiocarbon analyses.  Cores M-17, MNTKI-13 and M-18 cover the last 250, 260 and 200 years, respectively, and include dark grey brown clayey – silt sized mud with some red brown mass-flow units and a coccolithopore ooze-bearing unit near the top. The lithological and geochemical correlation between the cores was done according to the chronology of the core MNTKI – 13 that was determined from radionuclide dating. Therefore, age models for the two other cores (M17 and M18) were created according to these correlations. Thus, the bottom of the coccolithopore ooze-bearing unit was dated at 1985 and it was revealed that this unit deposited between 1985 and 1995. Two mass flow units identified in cores M-18 and MNTKI-13 were probably originated from Kocadere delta during years 1985 and 1930 respectively.  The gray brown unit of MNTKI -13 deposited between years 1945 and 1950.  Enrichment of Ti and Zr and depletion of other lithophile crustal elements (Th, La, Nb ve Rb) in these units are due to heavy mineral (rutile, titanite and zirconium)-rich silt size detrital influx. The red – brown color and high magnetic susceptibility values (25 uSI) of the mass units indicate the presence of Fe-oxides. These mass flow units are characterized with increasing trends of elements such as K, Ti, Mn, Zr and Fe that are associated with terrigenous material input, whereas decreasing trends of Ca and total inorganic carbon content due to dilution of biogenic material input. On the other hand, the Ca and total inorganic carbon content increase in coccolithopore ooze bearing unit, whereas K, Ti, Mn, Zr and Fe content as well as magnetic susceptibility values decrease due to dominance of biogenic material deposition.  The gray – brown unit of MNTKI-13 which deposited between the years 1945 and 1950 reveal low magnetic susceptibility, high Ca and total inorganic carbon content and is distinguished in the radiography as a dark color band. These results indicate that this unit is a diagenetic carbonate cementation zone.    Increase of TOC to 4 % in the coccolith ooze unit follows the establishment anoxia in bottom waters soon after the year 1965.  The origin of organic matter that was deposited after the year 1995 is of terrestrial end-member, whereas it is of marine end – member in the coccolithopore unit that deposited between the years 1985. A high content of terrestrial organic matter (C/N = 50) is transported to the centre of the Gemlik Bay with the 1930 mass flow. Algal blooms after 1985 indicate high nutrient input (N and P) and eutrophication caused by industrial and domestic discharge to the gulf as well as sewage and fertilizers used in agricultural activities. High organic matter content and nutrient input to the Gemlik gulf leading to the organic pollution since 1930s is caused mainly by the industries in the gulf area such as Sümerbank Filature Factory built in 1937, olive oil and fertilizer production. Therefore the anoxic conditions that developed at the sea bottom after the year 1965 which is also revealed by the Mn depletion onset in sediments, is caused by the high rate of organic matter input from industrial and domestic effluents that are consuming oxygen in water column coupled with the natural stratification in water column preventing the renewal of oxygen. Hence, both of these processes lead to oxygen deficiency in bottom waters. δ15N content is relatively higher after year 1930, reaching maximum values during the last 40 years in the gulf. If the oxygen levels decrease in bottom waters and the conditions become reducing, the reduction of NO3- leads the remnant NO3- to be enriched in δ15N. Because the denitrifying bacteria prefers the light isotope to heavy isotope (isotope fractionation) for its metabolism during nitrate reduction reaction (denitrification) for obtaining energy. Such high δ15N values indicate that denitrification has been an important process after 1930s until present, in relation with anoxic bottom water conditions. Low δ15N contents between the years 1830 – 1930 (‰ 2,5-3) indicate that the denitrification was not so common and the bottom waters were relatively more oxic. The oxygen content in waters increases due to decreasing temperatures and consequently increasing rate of water circulation. Relative enrichment of K, Rb and Li during 1840 -1980 indicate that relatively arid climatic conditions prevented forest expansion and lead to the erosion that transported these lithophile elements to the gulf within clastic minerals. Their depletion during the last 40 years indicate more humid climate conditions and more precipitation leading to forest expansion and less erosion. These results are supported by climatic δ18O data from a lake in the central part of Turkey. Similarly K, Ti, Fe and Zr show decreasing trends during approximately 1915 according to the XRF data, in cores M-17 and M-18. This depletion period is correlated with the increasing precipitation identified from the δ18O curve from the same lake.   The origin of crustal - derived, lithophile elements in Gemlik Gulf sediments such as Rb, Li, Ti, Nb, La, Zr and Th is felsic gneiss and granites of Paleozoic - Triassic age of Karakaya unit and granites of Oligo - Miocene age that outcrop in Armutlu peninsula and the surrounding region.  Concentrations of heavy metals such as As, Sb, Bi, Cu, Pb, Zn, Cd and Th increase abruptly after 1975 due to anthropogenic pollution. Cd is significantly enriched (enrichment faxtor, EFmax= 6) among them, whereas the enrichments of Zn and Sb are moderate (EF=2.2 – 2.3) , with all heavy metal concentrations rising above treshold level (EF=2) starting around the year 1980. Geoaccumulation index (Igeo) values show a similar trend with enrichment factors (EFs) according to the onset of pollution. Geoaccumulation index of Cd reaches above extreme pollution treshold (Igeo=5) in 1995 followed by a decreasing trend up to present.  Mo (EFmax= 50), together with U (EFmax =3), S (EFmax = 3.6), and Sb, is highly enriched after 1965, which is due in part to diagenesis under anoxic bottom waters and in part to increased anthropogenic pollution. Calcophile semi-metals such as S, As, Zn, and Sb as well as elements such as Mo and U become enriched under anoxic bottom water conditions. Increasing total organic carbon content (up to 4% in coccolithopore ooze bearing unit) as well as depletion of Mn in sediments indicate development of anoxic conditions. Thus, Mo, and S shows high correlation with total organic carbon content. The onset of enrichment of Mo and S indicate the onset of anoxic bottom water conditions development as 1965. Because Mo, and uranium precipitates with sulphur and become enriched in sediments under reducing conditions.  The enrichment of Cd, Mo and Th in Gemlik Gulf sediments is also possibliy, partially caused by the usage of phosphate fertilizers for agriculture in Gemlik Gulf drainage basin. Because phosphate fertilizers contain these elements.
Heavy Metal And Organic Pollution And Its Temporal Evolution In Sediments Of Gemlik Gulf
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Ağır Metal Kirliliği; Organik Üretim; Toplam Organik Karbon; Zenginleşme Faktörü; Heavy Metal Pollution; Organic Productivity; Total Organic Carbon; Enrichment Factor